(untitled) (Journal of Contemporary Issues in Accounting, 2023)
The study investigated the impact of economic governance on socio economic development of Nigeria for the period 2005-2019. Economic governance was proxied by effective governance index, corruption control index, quality budgetary and financial management index and public administration index. The dependent variable socio economic development was measured by GDP growth rate. Four objectives were developed to pilot the study. Data were generated from secondary source from the World Bank data base. Analysis was carried out with E-view 10 statistical tool and methods of data analysis include: Augmented Dickey Fuller Unit root test, Autoregressive Distributed Lag (ARDL) model. Results of the unit root showed that data used were stationary, the ARDL regression model revealed that economic governance indices proxied by effective governance index, corruption control index, quality budgetary and financial management index and public administration index have not significantly impacted on GDP growth rate to effect socio economic development in Nigeria for the period in view. The study recommends that Good economic governance which will translate to improved formulation and implementation of sound micro and macroeconomic policies is vital for socio economic development.